The Interaction Effect of Personality Factor on Capability and Competence Requirement - Mansour, Ala’a Zuhair; Ahmi, Aidi; Popoola, Oluwatoyin Muse Johnson (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The auditing and accounting profession recently faced many challenges following fraudulent practices among the Jordanian public sector. The continuation of such fraudulent activities in the public sector impedes national economic developments and growth. This study’s main objective is to have a practical and effective way of reducing the incidences of fraud in the Jordanian public sector. Specifically, this research explores the moderating role of neuroticism on knowledge requirements and fraud risk assessment performance in the Jordanian public sector. Adopting a survey method, the respondents of this study are forensic accountants and auditors in the Jordanian public sector. The research findings will contribute to the existing literature on forensic accountants, auditors, knowledge capability requirement, and neuroticism as a personality factor and fraud risk assessment performance of regulators regarding prevention and detection of fraud in the Jordanian public sector work environment.